A case report of eosinophilic granuloma in axis (C2) vertebra causing spinal cord compression - Som, R S Chitra; Rudrappa, Satish (Indian Journal of Case Reports, 2020)
Eosinophilic granuloma (EG), a benign osseous variant of Langerhans cell histiocytosis, is rarely observed in cervical spine and being in axis (C2) is even more infrequent. We present here an unusual case of EG of the axis vertebra with neurological impairment due to cervical cord compression, where the patient underwent decompression, C1–C2 spinal stabilization and steroid therapy. Cervical vertebrae involvement of EG with cord compression and neurological deficit is very unlikely, and this case report contributes to the clinical experience of this rare but highly prodigious disease. The benefit of surgical treatment with total removal of the tumor and spinal stabilization to prevent irreversible neurological deficit is emphasized.